Seasonal and Spatial Analysis of Air Pollutants Emissions from Fuel-Wood Utilization in Selected Rural Communities within Odeda LGA, Nigeria (Global Journal of Science Frontier Research, 2016)
The effects of fuel-wood utilization on spatial and temporal concentration of air pollutants were assessed in 12 purposively selected rural communities in Odeda Local Government Area of Ogun state. Carbon (II) oxide (CO), Carbon (IV) oxide (CO 2 ), Sulphur (IV) oxide (SO 2 ), Nitrogen (IV) oxide (NO 2 ), Methane (CH 4 ) and Particulate Matter of 2.5 (PM 2.5 ) and 10 (PM 10 )were monitored at 0, 2 and 5 m away from the cooking points using active air samplers in dry and wet seasons. Data collected were subjected to descriptive, ANOVA and Correlation statistics at 0.05 significant level.
Keywords: dirty energy; ambient environment; air quality; spatio-temporal concentrations